Standardization of Records in Orthodontics Part 2: Craniofacial Imaging Techniques - Faruk İzzet Uçar; Ahmet Ercan Şekerci; Tancan Uysal; Ali Osman Bengi (Galenos Yayinevi, 2012)
Today, because of the greater usage of the two dimensional and three dimensional imaging records in orthodontic clinics; properties, standardization, and indications of these imaging will be mentioned in the present review.Imaging in orthodontics have great importance in diagnosis, treatment planning and treatment outcomes. Orthodontic imagines were divided into two separate categories: conventional or two dimensional and three dimensional imagines. In the present study, both methods will be discussed.